Potato varieties (Solanum tuberosum L.) determined the drought tolerance using the plastic cover (Mongolian Journal of Agricultural Sciences, 2021)
Selecting potato varieties which is drought-tolerant is one important way to reduce the risk of drought. Field experiments were conducted at potato research field located in the Institute of plant and agricultural science, Mongolia. In this experiment used the Gala, Soloist and Quarta varieties. total of 120 plants which is 40 bulbs from one variety were evaluated the drought tolerant. When we used the plastic cover from the tuber initiation to the bulking stage. The total harvest of potato decreased by 9.2 t/ha on average. The total harvest of potato decreased by 9.2 t/ha on average. When using the plastic cover, Potato harvest is decreased by 3.4 t/ha and tubers of production is decreased by 3.5 t/ha. The weight of non-standard tubers is closely related to the yield of varieties grown in drought conditions (r = 0.89), which accounts for the majority of the total yield by the weight of non-standard tubers. The Production tubers of Gala varieties is more 46.4 percent than the average varieties of potato. Lack of soil moisture decreases at the above stage of potato cultivation reduces the yield by 20-30%, reduces the growth rate, reduces the size and weight of the tubers, and has a significant negative impact on crop growth.Гандаавч ашиглан төмс (Solanum tuberosum)-ний сортуудын ган тэсвэрийг тодорхойлсон дүнГанд тэсвэртэй сортыг шалгаруулж тарих нь гангийн эрсдэлийг багасгах нэг арга гэж эрдэмтэд үзсээр байна. Туршлага судалгааг УГТХүрээлэнгийн Төмс судлалын туршлагын талбайд Гала, Солист, Куарта сортыг хамруулж нэг сортоос 40 булцуу нийт 120 ургамалд ган тэсвэрийг  үнэлэв. Төмсний таримлын хөгжлийн үе шат болох бундуйлалтаас бүрэн цэцэглэлтийн үе шатанд нь талбайн нөхцөлд гандаавч ашиглахад таримлын нийт ургац дунджаар 9.2 т/га буюу гандаавч ашиглаагүй талбайн ургацаас 3.4 т/га, таваарын булцууны ургац 3.5 т/га тус тус буурсан байна. Гандаавчтай нөхцөлд ургасан сортуудын ургацад стандарт бус булцууны жин нягт (r=0.89) хамааралтай байгаа нь нийт ургацын дийлэнх хувийг стандарт бус булцууны жин эзэлж байна. Гала сорт нь таваарын булцууны ургацаар сортуудын дунджаас 46.4 хувиар илүү байв. Төмсний таримлын дээрх үе шатанд хөрсний чийгийн хангамж дутагдалтай байвал ургац 20-30% буурч, ургах эрчим багасч улмаар булцууны хэмжээ жижгэрч, жин буурч таримлын өсөлт хөгжилтөнд ихээхэн сөрөг нөлөө үзүүлдэг байна. Түлхүүр үг:  Гала, Солист, Куарта, булцуу, ургац